2012
DOI: 10.1371/journal.pone.0043671
|View full text |Cite
|
Sign up to set email alerts
|

ING1 and 5-Azacytidine Act Synergistically to Block Breast Cancer Cell Growth

Abstract: BackgroundInhibitor of Growth (ING) proteins are epigenetic “readers” that recognize trimethylated lysine 4 of histone H3 (H3K4Me3) and target histone acetyl transferase (HAT) and histone deacetylase (HDAC) complexes to chromatin.Methods and Principal FindingsHere we asked whether dysregulating two epigenetic pathways with chemical inhibitors showed synergistic effects on breast cancer cell line killing. We also tested whether ING1 could synergize better with chemotherapeutics that target the same epigenetic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 46 publications
1
29
0
Order By: Relevance
“…Since ING1 and ING2 are very closely related evolutionarily [43] and functionally [4], it is likely that both target the Sin3A HDAC complex to chromatin locales containing relatively higher density of the H3K4Me3 chromatin mark. This mechanism is consistent with recent observations that the epigenetic targeted drugs 5-azacytidine and the LBH589 HDAC inhibitor can act additively, or in some cases synergistically with ING1 in killing cells in breast cancer cell and animal models [20]. Data generated in this study provide mechanistic insight into why breast cancer cells may be selectively sensitive to HDAC inhibitors compared to normal breast epithelium; down-regulation of ING1 would already reduce the ability of cancer cells to accurately target the Sin3A complex and so treatment with HDAC inhibitors such as SAHA that selectively target ING2 and/or ING1 would be expected to have greater effects upon the epigenomes of cancerous versus normal epithelial cells.…”
Section: Discussionsupporting
confidence: 92%
“…Since ING1 and ING2 are very closely related evolutionarily [43] and functionally [4], it is likely that both target the Sin3A HDAC complex to chromatin locales containing relatively higher density of the H3K4Me3 chromatin mark. This mechanism is consistent with recent observations that the epigenetic targeted drugs 5-azacytidine and the LBH589 HDAC inhibitor can act additively, or in some cases synergistically with ING1 in killing cells in breast cancer cell and animal models [20]. Data generated in this study provide mechanistic insight into why breast cancer cells may be selectively sensitive to HDAC inhibitors compared to normal breast epithelium; down-regulation of ING1 would already reduce the ability of cancer cells to accurately target the Sin3A complex and so treatment with HDAC inhibitors such as SAHA that selectively target ING2 and/or ING1 would be expected to have greater effects upon the epigenomes of cancerous versus normal epithelial cells.…”
Section: Discussionsupporting
confidence: 92%
“…MDA-MB-468 breast cancer cell line that we have shown is sensitive to ING1-induced apoptosis [40]. As shown in Figure 7, transfection with a GFP expression construct resulted in 20% of transfected cells undergoing apoptosis while GFP plus ING1 expression induced apoptosis in 80% of the cell population.…”
Section: Resultsmentioning
confidence: 80%
“…Solid tumour size reduction upon 5-azaC treatment was observed in several studies using mice models of breast (Thakur et al, 2012) and spleen tumours (Mikyskova et al, 2014). Lindner et al demonstrated that 5-azadC treatment reduces tumour vascularization as well as tumour volume (Lindner et al, 2013).…”
Section: -Azac and 5-azadc Effects On Solid Tumoursmentioning
confidence: 98%